2017
DOI: 10.1186/s13000-016-0589-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Cks1 protein is associated with lymph node metastasis and poor prognosis in nasopharyngeal carcinoma

Abstract: BackgroundThe Cks1 protein is an essential factor in regulating cell cycle by mediating the ubiquitination of CDK inhibitor p27kip1. It has been reported that aberrant expression of Cks1 and p27kip1 proteins was found in various tumors and related to initiation and progression of carcinomas. However, the potential roles which Cks1 and p27KIP1 proteins play in NPC remain unclear. This study aims to examine the expression status of Cks1 and p27kip1 and their possible prognostic significance in NPC.MethodsParaffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Cyclin-dependent kinase regulatory subunit 1B (CKS1B) is a member of the Cks/Suc1 family of small proteins (9-18 kDa) that bind the catalytic subunit of cyclin-dependent protein kinases and regulate their function (9). Elevated expression of CKS1B has been associated with increased p27 (Kip1) turnover and cell proliferation, and poor prognosis in numerous tumor types, including oral, gastric, breast and colon carcinoma (10). Overexpression of CKS1B also activates the mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) signaling pathway (11).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin-dependent kinase regulatory subunit 1B (CKS1B) is a member of the Cks/Suc1 family of small proteins (9-18 kDa) that bind the catalytic subunit of cyclin-dependent protein kinases and regulate their function (9). Elevated expression of CKS1B has been associated with increased p27 (Kip1) turnover and cell proliferation, and poor prognosis in numerous tumor types, including oral, gastric, breast and colon carcinoma (10). Overexpression of CKS1B also activates the mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) signaling pathway (11).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its relevance for hepato-and/or cholangiocarcinogenesis is yet to be unveiled. Additionally, CKS1B represents an oncogene that has been reported increased in retinoblastoma, HCC, nasopharyngeal carcinoma and multiple myeloma [63][64][65][66][67]. Importantly, CKS1B upregulation has been positively related to increased proliferation, migration, angiogenesis, invasion and chemoresistance, being further related with lymph node metastasis and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…and data. Finally, 19 studies (Bochis et al, 2017;Brożyna et al, 2018;Kawakami et al, 2007;Kitajima et al, 2004;Lee et al, 2013;Li et al, 2007;Liu et al, 2008;Masuda et al, 2003;Miyai et Xu et al, 2017;Zolota et al, 2010) were identified with a total of 2,224 patients in this metaanalysis ( Figure 1). The sample size for the enrolled studies ranged from 30 to 482 patients and the mean sample size was 117.1 patients.…”
Section: Main Information Of the Included Studiesmentioning
confidence: 80%